The effect of electronic auditing in reducing audit risks and improving the quality of the auditor’s report: an exploratory Study to opinions of a sample of auditors working in Iraqi banks - talib abdulameer alshammari, Mushtaq (Iraqi Journal for Administrative Sciences, 2023)
This research aims to show the role that the electronic auditing can play in reducing the risks that arising from auditing process, and also helping to improve the quality associated with the auditor’s report through providing efficient internal control systems which can prevent the occurrence of violations and errors or reduce them to the minimum level, and providing suitable accounting systems specialized with information that can help to serve all users. This research has been applied in the Iraqi banking sector by designing a survey form consort with the goal of the research as well as its hypotheses, and in order to work on analyzing the research data and proving or denying its hypotheses, appropriate statistical tools have been used for this purpose. This research reached to conclusions of which the electronic auditing can help reduce audit risk in order to improve the quality associated with the auditor's report.